White light emission from a single organic molecule with dual phosphorescence at room temperature - Zikai He (Nature Portfolio, 2017)
The development of single molecule white light-emitters is extremely challenging for pure phosphorescent metal-free systems at room temperature. Here the authors show a single pure organic room temperature phosphor, 4-chlorobenzoyldibenzothiophene, utilizing the emission from both T1 and T2 states.